The Impacts of Multiple Simultaneous Climate Variations - Ilczuk,Richard Jr E (2016)
Climate variationssuch as El NioLa Nia (ENLN), the MaddenJulian Oscillation (MJO), and the Arctic Oscillation (AO)have significant impacts on environmental conditions and operatingenvironments around the globe. However, relatively little is known about how climate variations interact and alter each others impacts. We used several multi-decadal reanalysis data sets to investigate the interactions between ENLN and MJO events. We analyzed the interactions by season, and by event amplitude and phase. We found substantial constructive and destructive interference between the tropical convection and subsidence centers of ENLN and MJO events, and the tropical and extratropical lowfrequency wave responses to the events. This interference causes large differences in the anomalies that are commonly thought to characterize the eventsfor example, changes in the patterns, locations, magnitudes, and even signs of the wind, precipitation, and ocean surface wave anomalies associated with EN, LN, and the eight MJO phases. Our results indicate that analyses and forecasts of one type of climate variation need to account for the simultaneous occurrence of other types of climate variations. The data sets, methods, and results of this study will be used to improve operational climate and long range support products.